Bioinformatics analysis of microRNA linked to ubiquitin proteasome system in traumatic osteonecrosis of the femoral head. Issue 33 (14th August 2020) - Chen, Ning; Xiao, Bolian; Wang, Shiying; Wei, Biaofang
Abstract : Abstract: MicroRNAs (miRNAs) have been suggested to act critical roles in the pathophysiology of traumatic osteonecrosis of the femoral head (TONFH). Unfortunately, their roles in the development of TONFH are still ambiguous. The purpose of this study is to identify promising miRNA biomarkers in traumatic osteonecrosis development. We conducted a comprehensive bioinformatics analysis using microarray datasets downloaded from the Gene Expression Omnibus database, and compared the expression of miRNAs in the serum of TONFH patients with controls. Next, we performed target prediction, function enrichment analysis, and protein-protein interaction network analysis based on differentially expressed (DE) miRNAs. We identified 26 DE miRNAs that may contribute to the pathophysiology of TONFH. The miRNAs were linked to ubiquitin proteasome system including conjugating protein ligase activity, ubiquitin-protein ligase activity and ubiquitin mediated proteolysis 5 pathway, and we exposed miR-181a-5p and miR-140-5p as promising biomarkers in TONFH. A predicting model consisting of 5 miRNAs may help discriminating high-risk patients who might develop TONFH after femur neck fracture. Among DE miRNAs, MiR-181a-5p and miR-140-5p may contribute to the development femoral head osteonecrosis after femur neck fracture via ubiquitin proteasome system.